SUMMARY OF RESULTS IN RESEARCH PAPERS OF BEHAVIOURAL SCIENCES - Ramos-Álvarez, Manuel Miguel; Catena Martínez, Andrés (Anales de Psicología / Annals of Psychology, 2005)
The main aim of this paper is the application of recent methodological developments in order to write adequately the results section of research papers, particularly in the field of Psychology and other behavioural sciences. Thus, we illustrate some general issues about how the information should be summarized, emphasizing the need to explain in detail the choice of the error measure. The second part of the paper introduces more specific issues, as the adaptation of the error variability with reference to two parameters: the research design and the degree of generalization of the research hypothesis. This paper concludes with an applied example of the above issues, including some brief remarks about the way to add error bars to figures and graphics using a spread sheet program (i.e. Microsoft Excel©).